The Mariner’s Centre of Gravity: The Self - ur Rehman, Mustaq; Zahid Ali Shah, Syed; Ashfaq, Samina (The Journal of Humanities & Social Sciences, 2023)
Modern day selfishness and senselessness has imperatively necessitated the quest for the true “Self.” Bereft of his true identity in the confused milieu of modern times, man frantically searches for a perennial culture of which he was mythically a part and where he was firmly rooted. The search is not external but rather internal; it is to be carried out within the inner recesses of mind and not in the external social life; it does not relate to human life in social progress but in his archetypal realities that are the cornerstones of eternal human psyche. With us today it is the internal world that is desolate and uninhabited. The strong desire, which was once with the man of yore to gather ourselves into the interiority of a rare world of values and convictions, has given way to the uncertain preoccupations of which we hardly feel ourselves as part. The Mariner’s story in Coleridge’s “The Rime of the Ancient Mariner” relates a similar account that can be accounted for Man’s eternal quest for wholeness.